Real Intrest Rate and Growth: An Empirical Note - Antonello Eugenio Scorcu; Carlo D'Adda (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
Are restrictive monetary policies harmful to growth? The note aims at providing some empirical evidence to answer the question. A significant negative correlation between growth and real interest emerges over the period 1960-94; in the eighties this relationship strengthens. This result is in agreement with the traditional view of a long run positive link between growth and capital accumulation and a negative long run link between accumulation and the cost of capital. Moreover the outcome is in line with the view that links the slowdown in economic growth of the industrial countries over the last decades appears to the implementation of restrictive monetary policies
Keywords: 330